Anaerobic digestates lower N2O emissions compared to cattle slurry by affecting rate and product stoichiometry of denitrification – An N2O isotopomer case study. (May 2015) - Köster, Jan Reent; Cárdenas, Laura M.; Bol, Roland; Lewicka-Szczebak, Dominika; Senbayram, Mehmet; Well, Reinhard; Giesemann, Anette; Dittert, Klaus
Abstract: Assessing effects of organic fertilizer applications on N2 O emissions is of great interest because they can cause higher N2 O emissions compared to inorganic fertilizers for a given amount of added nitrogen (N). But there are also reports about enhanced N2 O reduction to climate-neutral elemental N2 after application of organic manures to soils. Factors controlling the N2 O/(N2 O + N2 ) product ratio of denitrification are interrelated, and also the ratio is difficult to study because of limitations in N2 flux measurements. In this study, we investigated N2 O and N2 emissions from soil treated with organic fertilizers with different C/N ratios. An N2 O isotopomer approach combined with conventional N2 O and N2 flux measurements was employed to study underlying microbial pathways. A grassland soil was amended with anaerobic digestate (AD) from food waste digestion (low C/N ratio) or cattle slurry (CS; high C/N ratio), respectively, adjusted to 90% WFPS, and incubated for 52 days under helium–oxygen atmosphere (10% O2 ) using a soil incubation system capable of automated N2 O, N2, and CO2 measurements. N2 O isotopomer signatures, i.e. the δ 18 O and SP values (site preference between 15 N at the central and the peripheral position in the N2 O molecule), were determined by Isotope Ratio Mass Spectrometry and used to model and subsequently estimate the contribution of bacterial denitrification and autotrophic nitrification to N2 O production. For this approach the direct determination of emitted N2 is essential to take isotope effects during N2 O reduction to N2 into account by correcting the measured isotope signatures for isotope effects during N2 O reduction using previously determined fractionation factor ranges. The addition of both organic fertilizers to soil drastically increased the rate of gaseous N emissions (N2 O + N2 ), probably due to the effects of concurrent presence of nitrate and labile C on the denitrification rate. In the initial phase of the experiment (day 1 to ∼15), gaseous N emissions were dominated by N2 fluxes in soils amended with organic manures; meanwhile, N2 O emissions were lower compared to untreated Control soils, but increased after 15–20 days relative to the initial fluxes, especially with CS. Extremely low N2 O, but high N2 emissions in the initial phase suggest that reduction of N2 O to N2 via denitrification was triggered when the soil was amended with organic fertilizers. In contrast in the untreated Control, N2 O release was highest during the initial phase. Total N2 O release from AD treated soil was similar to Control, while N2 O from CS treated soil was considerably higher, indicating that denitrification was triggered more by the high labile carbon content in CS, while the cumulative N2 O/(N2 O + N2 ) product ratio and thus N2 O reduction were similar with both organic fertilizers. The results of the N2 O source partitioning based on the isotopomer data suggest that about 8–25% (AD) and 33–43% (CS) of the cumulated N2 O emission was due to nitrification in organically amended soil, while in the untreated Control nitrification accounted for about 5–16%. The remaining N2 O production was attributed mainly to denitrification, while the poor model fit for other source pathways like fungal denitrification suggested their contribution to be of minor importance. The observed rather distinct phases with predominance first of denitrification and later of nitrification may help developing mitigation measures by addressing N2 O source processes individually with appropriate management options. The observation of relatively large shares of nitrification-derived N2 O is surprising, but may possibly be related to the low soil pH and will require further investigation. The determination of N2 production is essential for this isotopomer-based source partitioning approach, but so far only applicable under laboratory conditions. The results of this study indicate that the combination of N2 O δ 18 O and SP values is very useful in obtaining more robust source estimates as compared to using SP values alone. Highlights: 52 days incubation of organically amended soil under denitrifying conditions. Direct N2 and N2 O measurements by GC, N2 O isotopomer analysis by IRMS. Anaerobic digestate from food waste led to lower N2 O emission than dairy slurry. Organic fertilizers enhanced N2 O reduction to N2 compared to untreated soil. Up to 40% of N2 O came from nitrification, despite conditions favoring denitrification.